Associations between Fall Distance, Age, and Trauma Outcomes in Older Adult Patients - Berg, Gina M.; Hervey, Ashley M.; Lee, Felecia A.; Holmes, Sarah; Keuter, Kayla R.; Harrison, Paul B. (Kansas Journal of Medicine, 2019)
Introduction. Falls are the leading cause of injury death amongolder adults. This study sought to determine if there are differencesbetween fall distance (ground level vs greater than groundlevel) and age (old vs very old) in terms of in-hospital mortality,orthopedic consultations, and neurological consultations.Methods. A retrospective trauma registry review was conductedof older adult patients (aged > 65 years), admitted to aMidwestern Level I trauma facility (2005 - 2010) due to a fall.Results. Of the 1,064 patients analyzed, the majority fell fromground level compared to greater than ground level (64% and36%, respectively). Median age was 80 years. Fall distance wasnot associated significantly with in-hospital mortality (OR0.88; CI 0.50 - 1.54) or neurological consultations (OR 1.02; CI0.72 - 1.43), but was associated with orthopedic consultations(OR 1.49; CI 1.09 - 2.04). Age was not associated with in-hospitalmortality or neurological or orthopedic consultations.Conclusions. Fall distance was not associated with in-hospitalmortality or receiving a neurological consultation.However, older adults who fell from greater than groundlevel were more likely to receive orthopedic consultations.There were no differences in in-hospital mortality or receivinga neurological or orthopedic consultation based onage. These findings indicated that as the older adult populationincreases, burden of care will increase for trauma centersand neurological services. KS J Med 2016;9(3):54-57.